2016
DOI: 10.1002/jcla.22003
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Activity of Cyclooxygenase‐2 in Tissue and Serum of Patients With Cervical Cancer

Abstract: Augmented Cox-2 activity is implicated in the pathogenesis of cervical cancer, and its serum level could serve a potential to distinguish this malignancy. Therefore, it is suggested that serum Cox-2 may be useful in monitoring the diagnosis and treatment outcome of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…12 An accumulation of evidence indicates that the overexpression of COX-2 in cervical carcinoma tissues is involved in the pathogenesis of cervical cancer. 13 This is consistent with a previous study, in which the polysaccharide obtained from G. lucidum regulated Bcl-2, Bax, and cleaved caspase-3 protein expression and exerted antitumor activity against HL-60 acute leukemia cells. 14 Therefore, we speculated that EGLP may inhibit tumor development via an increase in the expression of Bax and cleaved caspase-3, and a decrease in the expression of Bcl-2 and COX-2.…”
Section: Discussionsupporting
confidence: 93%
“…12 An accumulation of evidence indicates that the overexpression of COX-2 in cervical carcinoma tissues is involved in the pathogenesis of cervical cancer. 13 This is consistent with a previous study, in which the polysaccharide obtained from G. lucidum regulated Bcl-2, Bax, and cleaved caspase-3 protein expression and exerted antitumor activity against HL-60 acute leukemia cells. 14 Therefore, we speculated that EGLP may inhibit tumor development via an increase in the expression of Bax and cleaved caspase-3, and a decrease in the expression of Bcl-2 and COX-2.…”
Section: Discussionsupporting
confidence: 93%
“…In recent years, attention has been focused on understanding the role of inflammation in tumour biology. It is known that COX-2 plays an important role for the induction of inflammation either individually or through sustained production of PGE 2 [ 18 ]. The overexpression of COX-2 is reported in numerous human malignancies including colon, breast, lung, and prostate [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…COX-2 inhibitors may participate in the occurrence and development of tumors through enhancing tumor nourishing angiogenesis, inhibiting immune surveillance, promoting cell proliferation, enhancing tumor invasion/metastasis or inhibiting apoptosis and therefore they are associated with the prognosis of patients with tumors (8). Studies have demonstrated that COX-2 is not expressed in normal cervical tissues, but that its expression in CC is significantly increased (9). Consequently, COX-2 inhibitors have become a focus of CC therapies (10).…”
Section: Introductionmentioning
confidence: 99%